2021
DOI: 10.3389/fcimb.2021.666030
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterisation of Colistin Resistant Klebsiella pneumoniae Clinical Isolates From North India

Abstract: BackgroundIncreasing use of colistin has led to the world-wide emergence of mobile colistin resistant gene (mcr). The present study aimed to identify and characterise mcr and other drug-resistant genes in colistin resistant Klebsiella pneumoniae clinical isolates.MethodsTwenty-two colistin resistant K. pneumoniae were analysed for mcr and other drug-resistant genes, efflux pumps, and virulence genes, and for their biofilm forming ability. Pulsed-field gel electrophoresis (PFGE) and multi-locus sequence typing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…bla VIM and bla KPC were not found among these five isolates. Singh et al (2021) reported that all the isolates harboring mcr-1 in their study co-harbored bla OXA-48 . Han et al (2020) reported the identification of the XDR E. coli clinical isolate co-harboring mcr-1 and bla NDM-1 .…”
Section: Discussionmentioning
confidence: 85%
“…bla VIM and bla KPC were not found among these five isolates. Singh et al (2021) reported that all the isolates harboring mcr-1 in their study co-harbored bla OXA-48 . Han et al (2020) reported the identification of the XDR E. coli clinical isolate co-harboring mcr-1 and bla NDM-1 .…”
Section: Discussionmentioning
confidence: 85%
“…The isolates were resistant to colistin but we could not detect mcr gene in any of the isolates possibly because the isolates harboured the chromosomal mutations leading to colistin resistance which we did not analyze. In a recent study from our centre we have reported K. pneumoniae ST16 harboring mutations in chromosomal gene mgrB ( Singh et al., 2021 ). Multi-locus sequence typing results revealed that the 5 K. pneumoniae isolates belonged to 3 different sequence types, ST101, ST16 and ST11.…”
Section: Discussionmentioning
confidence: 99%
“…The resistance mechanisms in the 5 K. pneumoniae isolates were analyzed using polymerase chain reaction to detect the genes encoding carbapenemases ( bla NDM , bla KPC , bla OXA-48 , bla IMP , bla VIM ), ESBLs ( bla CTX-M ), other class A β-lactamases ( bla SHV , bla TEM ) and colistin resistance genes mcr-1 , mcr-2 and mcr-3 using previously described methods and primers ( Singh et al., 2018 ; Singh et al., 2021 ). Following isolates from our previous studies were used as positive controls: K. pneumoniae CR kp 21 and CR kp 22 for bla NDM , bla OXA-48 , bla IMP , bla VIM , bla CTX-M , bla SHV , bla TEM ( Singh et al., 2021 ) while K. pneumoniae CRL3 for mcr gene ( Singh et al., 2018 ). Positive control for bla KPC gene was not available.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately reports revealing resistance to this drug are also coming up in the literature as we saw in our study and the same has also been reported from our neighbouring countries like Iran, China, and India. [22][23][24] Literature review has shown that some genetic modifications in chromosomal coding regions of some regulator genes have caused this phenotypic resistance to colistin. Regular genomic monitoring is required for all resistant isolates to see the colistin resistance.…”
Section: Miscellaneousmentioning
confidence: 99%